Embodying Love in the Inner City : Undoing Injustice through Intentional Neighboring - Katherine Hankins; Andy Walter; Traci Dahl (Transatlantica)
In many American cities, middle-class, faith-motivated individuals and families are moving into poor, inner-city neighborhoods to live out their vision of social justice in the city by becoming “intentional neighbors.” Drawing from the commandment to “love thy neighbor,” these faith-motivated actors develop relationships with their neighbors and share their resources in order to work towards the transformation of these places. In this paper we use the case study of participants in Mission Year, a Christian community-development organization, to examine the spatial and embodied practices that are integral to “doing justice” and demonstrating love in the inner city.